The Effectiveness of Bawaslu's Authority in Resolving Disputes in the 2024 Election Process in Central Sulawesi Province - Abdullah, Abdullah; S, Irzha Friskanov (Amsir Law Journal, 2025)
This study aims to analyze the authority of the Election Supervisory Agency (Bawaslu) in resolving disputes over the election process in Central Sulawesi Province using normative legal research methods. Disputes over the electoral process represent a critical dimension of democratic practice, yet previous studies have not sufficiently explored how the supervisory authority of Bawaslu functions in ensuring fairness and legal certainty in regional elections. This research examines the legal norms underpinning Bawaslu's authority, particularly as regulated in Law Number 7 of 2017 concerning General Elections and its implementing regulations, and evaluates the effectiveness of their application based on adjudicated dispute cases in the 2024 elections in Central Sulawesi. The findings indicate that although the Central Sulawesi Bawaslu has adjudicated several dispute cases and election violations, the implementation of its authority continues to face challenges related to institutional capacity, legal interpretation, and inter-agency coordination. The study underscores the significance of strengthening the legal framework and institutional resilience of Bawaslu to enhance its supervisory role in achieving fair and democratic elections in the future.